2020
DOI: 10.3390/ijerph17020507
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Chinese Diet Divergence from Chinese Food Pagoda and Its Association with Adiposity and Influential Factors: 2004–2011

Abstract: Nutrition transition in China has a strong impact on dietary quality and health of Chinese consumers. This study developed the diet quality divergence Index (DQD), the divergence between real food consumption and the Chinese food pagoda 2016 (CFP), to measure the quality of diet in China. Using four waves of data (2004, 2006, 2009, and 2011) from China Health and Nutrition Survey (CHNS), this study shed light on the transition of diet quality for Chinese residents. Results indicate that the DQD generally decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 60 publications
3
40
0
Order By: Relevance
“…In terms of the structure of the DQD, the largest part of the DQD comes from legumes and nuts. Its QDQ increases gradually from 2016 to 2019, consistent with the results found by Zhou et al (2020). The second largest part of the divergence derives from milk and milk products, which is followed by aquatic products, fruits and eggs.…”
Section: Data and Descriptive Statisticssupporting
confidence: 86%
See 3 more Smart Citations
“…In terms of the structure of the DQD, the largest part of the DQD comes from legumes and nuts. Its QDQ increases gradually from 2016 to 2019, consistent with the results found by Zhou et al (2020). The second largest part of the divergence derives from milk and milk products, which is followed by aquatic products, fruits and eggs.…”
Section: Data and Descriptive Statisticssupporting
confidence: 86%
“…We use the diet quality divergence (DQD) index as a proxy for diet quality. Following Zhou et al (2020), we calculate DQD as the absolute divergence value (percent) between real food consumption and recommended intake levels specified in the Chinese Food Pagoda (CFP) 2016. The CFP 2016 is illustrated in Chinese dietary guidelines 2016, which provides the daily recommended intakes of eight food categories for adults with age from 18 to 64 years old.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Zhou et al developed a standalone diet quality divergence Index (abbreviated as DQD(2) to distinguish from the DQD above) to assess the deviation of the diet from the CHFP [49]. They assessed data from 30,626 adults in the CHNS and demonstrated that, as BMI increased, the DQD(2) increased.…”
Section: The Dietary Balance Index (Dbi) and Obesity-related Outcomesmentioning
confidence: 99%